61. Geology of the Magma Mine Area, Arizona - Donald F. Hammer; Donald W. Peterson (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1968)
The Magma mine at Superior, Arizona, has produced over 13 million tons of ore yielding 1.5 billion pounds of copper. It is a mesathermal deposit, and, although the bulk of the ore has come from the Magma vein, most of the recent production has come from replacement deposits in limestone. The mine lies in a Precambrian and Paleozoic sequence of rocks that includes schist, diabase, quartzite, shale, and limestone; nearby, these rocks are intruded by igneous bodies of Mesozoic age that were probably the source of the ore-bearing fluids. Locally, these rocks are overlain by Cenozoic volcanic rocks and conglomerate. Layered rocks at the mine dip eastward about 30°. The area is extensively faulted, and surface faults are grouped into an earlier east-trending set and a later northtrending set. An additional set of diagonal faults that trends northwest and northeast is recognized underground. The east-trending Magma vein-fault, with its splits and branches, is the principal mineralized structure of the district. The bulk of the ore occurs in large ore shoots that plunge steeply westward and are sporadically connected by irregular ore shoots dipping gently eastward. The main ore controls apparently are selective zones of permeability related to the transverse faults. A bed of crystalline limestone near the base of the Martin Limestone (Devonian) is the host for the replacement ore bodies-discontinuous tabular pods dipping eastward parallel to the bedding. Selective permeability is again the apparent ore control, caused both by local hydrothermal solution of limestone and by deformation along faults. The principal copper minerals in the vein are chalcopyrite, bornite, enargite, tennantite, chalcocite, and digenite; these minerals vary in abundance according to a distinct zoning pattern. The upper part of the mine yielded considerable zinc as sphalerite, and the oxidized zone was rich in silver. The chief gangue minerals are pyrite, quartz, and hematite. In the limestone replacement bodies, chalcopyrite and bornite are the chief ore minerals.